RELATIONSHIP BETWEEN NEGATIVE COGNITIVE STYLE AND DEPRESSION AMONG MEDICAL STUDENTS - Perveen, Shagufta; Kazmi, Syeda Farhana; Rehman, Atiq Ur (Journal of Ayub Medical College Abbottabad, 2016)
Background: Depression is one of the major problems faced by medical students, which have significant adverse effects on their social, academic and occupational functioning. The objectives of the study were to estimate the prevalence of depression and to explore the gender differences and interrelationship between the depression and negative cognitive style among medical students of First year (FY) Last year (LY) MBBS. Methods: A Cross sectional questionnaire based study was conducted in Ayub medical college Abbottabad; Khyber medical college Peshawar; Bannu medical college; Rawalpindi medical college; Punjab medical college Faisalabad and Allama Iqbal medical college Lahore, Pakistan. Applying stratified sampling technique a battery of questionnaires naming depression screening test, self-report depression scale and cognitive style questionnaire was filed by a sample of 1000 (first and last year) medical students. The data was analysed by SPSS 16. Results: Positive relationship exists between depression and negative cognitive style (r=.57, p<.05) among medical students. Forty one percent male and 61% female students of FY and 58% males and 69% female of LY students exhibited depressive symptoms. Females have higher scores on cognitive style questionnaire t (998) =3.92, p<.05, and depression t (998)=4.89, p<.05. The t-test analysis also revealed that FY students were holding more negative cognitive style t (998)=53.09, p<.05, whereas LY medical students to be more depressed t (998)=5.14, p< .05. Conclusions: The study revealed significant distress among medical students. Negative cognitive style positively correlates with depression among medical students. Furthermore, it is noticed that among female students the prevalence of depressive symptoms and negative cognitive style was higher. Moreover, it is concluded that the prevalence of depression in LY and negative cognitive styles among FY was higher respectively. Students should be provided proper counselling to avoid and cope with faulty thought patterns leading to depression. Keywords: negative cognitive style, depression, gender